Foreign direct investment, financial development and economic growth in Africa: evidence from threshold modeling - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This paper investigates the role of local financial development in facilitating the materialisation of the growth-enhancing effect of foreign direct investment (FDI) in African countries. To this end, we improve on earlier studies by using a panel smooth transition regression model (PSTR) which is able to deal with heterogeneity issue associated with cross-country data. Based on a sample of 26 African countries over the period of 1990-2013, the results show that there is a minimum threshold level of financial development above which the growth-enhancing effect of FDI is unlocked in African countries. In other words, only countries that are located above a certain threshold level of financial development enjoy the growth-enhancing effect of FDI. These findings suggest that effort should be made by financial policymakers in African countries to improve the local financial markets conditions in order to extract the economic gains from FDI.
Keywords: Foreign direct investment; growth; absorptive capacity; financial development; panel smooth transition regression; Africa; ABSORPTIVE-CAPACITY; CAPITAL FLOWS; FDI; SPILLOVERS; NIGERIA